(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This scientific article examines the scientific basis of the name of the city of Samarkand, the architecture of industrial buildings and structures of Samarkand and expresses opinions about them. At the same time, information is given about the history of the formation of the city of Samarkand, the monuments and architecture of Samarkand, the culture of the city of Samarkand.